2012
DOI: 10.1097/meg.0b013e32834d09d4
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ types of celiac disease in Libyan children with type 1 diabetes mellitus

Abstract: Overall, biopsy-confirmed prevalence of CD was 11% (24 of 218). The present study confirms that CD in the Libyan type 1 diabetic population is high when compared with European and US studies, and for the first time we document that this population shares similar HLA-DQ2 genotype. This supports the theory regarding the role of the environment as an important factor in CD development in this part of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
12
1
2
Order By: Relevance
“…An increased risk of this haplotype combination has been reported in T1D w/CeD cohorts previously. The number of T1D w/CeD patients being DRB1*03:01‐DQB1*02:01‐DQA1*05:01/DRB1*04‐DQB1*03:02‐DQA1*03 heterozygous in our study is similar to the findings of Gutierrez‐Achury et al, which is higher than previously reported in several publications with 0‐21% being heterozygous . Although, not as high as the reported 66% by Larsson et al Most previous studies have included few individuals (<40), with the exception of Bakker et al reporting on 118 patients (92 of which were HLA typed), the publication by Gutierrez‐Achury et al using HLA tagSNPs on 543 patients, and Smigoc Schweiger et al presenting 130 patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An increased risk of this haplotype combination has been reported in T1D w/CeD cohorts previously. The number of T1D w/CeD patients being DRB1*03:01‐DQB1*02:01‐DQA1*05:01/DRB1*04‐DQB1*03:02‐DQA1*03 heterozygous in our study is similar to the findings of Gutierrez‐Achury et al, which is higher than previously reported in several publications with 0‐21% being heterozygous . Although, not as high as the reported 66% by Larsson et al Most previous studies have included few individuals (<40), with the exception of Bakker et al reporting on 118 patients (92 of which were HLA typed), the publication by Gutierrez‐Achury et al using HLA tagSNPs on 543 patients, and Smigoc Schweiger et al presenting 130 patients.…”
Section: Discussionsupporting
confidence: 87%
“…The number of T1D w/CeD patients being DRB1*03:01-DQB1*02: 01-DQA1*05:01/DRB1*04-DQB1*03:02-DQA1*03 heterozygous in our study is similar to the findings of Gutierrez-Achury et al, 22 which is higher than previously reported in several publications with 0-21% being heterozygous. 23,[31][32][33] Although, not as high as the reported 66% by Larsson et al 34 Most previous studies have included few individuals (<40), with the exception of Bakker et al 23 reporting on 118 patients (92 of which were HLA typed), the publication by Gutierrez-Achury et al 22 using HLA tagSNPs on 543 patients, and Smigoc Schweiger et al 21 presenting 130 patients. Our findings are in line with the 2 latter studies 21,22 that DRB1*03:01-DQB1*02:01-DQA1*05:01/DRB1*04-DQB1*03:02-DQA1* 03 heterozygous individuals with T1D show the highest risk of coexisting CeD.…”
Section: Discussionmentioning
confidence: 96%
“…Sixty‐two studies on the prevalence of CD in patients with type 1 diabetes were included in this review . The prevalence of EMA positivity ranged from 0% to 13.83%; that of elevated tTG levels ranged from 0.81% to 21.16%, while 0.40% to 12.16% showed villous atrophy, ‘flat biopsies’ or Marsh 3 histological changes.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study of T1DM children the biopsy‐confirmed prevalence of CD was 11% (24 of 218); among those with CD, 75% had HLA‐DQ2, 21% had HLA‐DQ2/DQ8, and 4% had HLA‐DQ8. In addition, the 70% carried HLA‐DQ2 linkage with HLA‐DRB1*03 . The prevalence of CD in T1DM has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 70% carried HLA-DQ2 linkage with HLA-DRB1*03. 52 The prevalence of CD in T1DM has been studied extensively. The Agency for Healthcare Research Report that included 21 studies and two additional studies reported that the prevalence of CD was 3-12%.…”
Section: Discussionmentioning
confidence: 99%